Kepadatan Tikus dan Ektoparasit yang Tertangkap di Pasar Jatingaleh dan Pasar Kedung Mundu Kota Semarang - Maibang, Whinda Gemaria; Martini, Martini; Santoso, Luthfi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
: Vector borne disease remains a public health problem and potential to cause an outbreak. Rats and ectoparasite causes health problems because its existence brought many seeds of disease. There are many potentially public places to find rats in large quantities, one of which is a traditional market. The purpose of this study was to accounter density of rats and ectoparasite were found in Jatingaleh traditional market and Kedung Mundu traditional market Semarang 2014. This study was descriptive research with survey method and cross sectional design. The method of study was by trapping rats and used live trap has been mounted roasted coconut for three days. The results of the study showed in Jatingaleh traditional market were found 26 tails of rats, and Kedung Mundu traditional market were found 14 tails of rats. Trap success in Jatingaleh traditional market (8,67%) greather than Kedung Mundu traditional market (4,66%). The ectoparasites were found on the bodies of rats in Jatingaleh traditional market species of flea Xenopsylla cheopis, species of lice Hoplopleura pacifica, species of mite Laelaps echidninus, and Kedung Mundu traditional market were found species of lice Hoplopleura pacifica, species of mites Laelaps turkestanicus and Laelaps nuttalli. Specific flea index in Jatingaleh traditional market as much 0,94, while in Kedung Mundu traditional market not found flea. Specific mite index in Jatingaleh traditional market (0,3) less than Kedung Mundu traditional market (11,5). From the results of this study It can be concluded that the Jatingaleh traditional market more potentially transmit disease sourced rat than Kedung Mundu traditional market related rat density and diversity ectoparasite. Rodents control program very important to do in both markets